ORGANOLOGI INSTRUMEN GAMBANG DALAM KESENIAN GAMBANG KROMONG PRODUKSI TOTONG DI RAWA KUCING, TANGERANG - Setyatama, Agung; Rustandi Mulyana, Aton (Jurnal Penelitian Musik, 2024)
This research discusses the study of gambang organology in the art of Gambang Kromong through the production of the Totong version of the gambang. Gambang is a Betawi traditional musical instrument in the form of a xylophone with a special wood called Merawan wood. This study aims to examine the organology of gambang based on observations, descriptions, and analysis of the aspects involved in it. The term organology comes from the ancient Greek "organon" which means tool, or in this case the manufacture of musical instruments, and "logos" science. So in simple terms orgonology is the study or science that studies musical instruments. In the production itself there are 4 things that must be considered, namely material, manufacture, adjustment, and maintenance. This Research was conducted using a qualitative descriptive analysis method, by presenting the facts that were then followed by analysis. The method used in this study was divided into four stages, namely data collection, data processing, data analysis, and drawing conclusions. Totong is one of the gambang craftsmen in the Tangerang area. The assembly stage itself goes through several stages, namely the preparation of tools and materials, design and formation, adjustment, until entering the finishing stage. In Organology we can study and analyze the relationship between organology (construction forms and production stages) and instruments when musical performances are used, of course there will be adjustments to improve the production quality of these musical instruments.